2012
DOI: 10.1021/la304074x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Interactions of C2 and C3 Polyols with γ-Al2O3 and the Role of Coadsorbed Water

Abstract: The formation of surface species from two- and three-carbon polyols on γ-Al(2)O(3) in the presence and absence of coadsorbed water is investigated. Aqueous-phase adsorption isotherms indicate that competitive adsorption between water and polyol inhibits the uptake of the polyol molecules on γ-Al(2)O(3) and that the polyol with the most hydroxyl groups, glycerol, experienced the greatest uptake. Deuterium solid echo pulse NMR measurements support the fact that glycerol strongly interacts with γ-Al(2)O(3) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
86
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 64 publications
9
86
5
Order By: Relevance
“…One should bear in mind though that the activity of water-tolerant Lewis acid sites will also be defined by the nature of the oxygenate molecule being converted. Copeland et al [65,66] studied the competitive adsorption of oxygenates with water on metal oxides and showed that the structure of the oxygenate molecule -carbon chain size and type, number and position of functional groups -can alter its interaction strength with the solid surface and its ability to replace water on surface sites. Water molecules (Lewis base) in the water-Lewis acid adducts can be displaced from the acid sites by a more basic oxygenate molecule, rendering an active Lewis acid site.…”
Section: Discussionmentioning
confidence: 99%
“…One should bear in mind though that the activity of water-tolerant Lewis acid sites will also be defined by the nature of the oxygenate molecule being converted. Copeland et al [65,66] studied the competitive adsorption of oxygenates with water on metal oxides and showed that the structure of the oxygenate molecule -carbon chain size and type, number and position of functional groups -can alter its interaction strength with the solid surface and its ability to replace water on surface sites. Water molecules (Lewis base) in the water-Lewis acid adducts can be displaced from the acid sites by a more basic oxygenate molecule, rendering an active Lewis acid site.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a better mechanistic understanding of which oxygen species participate in desired and undesired oxidation pathways is required to improve selectivity and atom-efficiency. Besides catalytic oxidation reactions, water-mediated proton transfer has other farreaching implications, for instance, in catalytic hydrodeoxygenation of bio-oil [72], electrocatalysis [73][74][75], and any reaction using solid acid catalysts including zeolites [76,77]. Thus, we see numerous opportunities for innovative research on water-assisted catalysis in diverse areas that may ultimately lead to disruptive technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of glycerol at an initial reactionp eriod of 2h as af unction of temperature is displayed in Figure 4. [40] We therefore assign the high activities of M-Al 2 O 3 and N-Al 2 O 3 to the fact that they have higher acid-site densitiest han C-Al 2 O 3 .M -Al 2 O 3 exhibits ah igher weaka cid site density and al ower strong acid site density than N-Al 2 O 3 ,a nd this couldd ecreaset he coking rate. Their initial conversionsf ollow the same order as their stabilities, as shown in Figure 4, that is, M-Al 2 O 3 > N-Al 2 O 3 > C-Al 2 O 3 .F or the glycerol dehydration reaction, the catalytic activities of zeolite materials are governed mainly by pore-confinement effects and the mesopore size, and the hydrophilic hydroxy-containing surface of g-Al 2 O 3 is governed mainly by acid-site density.…”
mentioning
confidence: 94%